SMA-based smart soft composite structure capable of multiple modes of actuation. (1st December 2015) - Rodrigue, Hugo; Wang, Wei; Bhandari, Binayak; Han, Min-Woo; Ahn, Sung-Hoon
Abstract: This paper introduces the design of a smart soft composite (SSC) actuator capable of multiple modes of actuation. This actuator combines four shape memory alloy (SMA) wires embedded in a soft matrix where one or two SMA wires can be activated to induce the actuator into either the bending mode, the twisting mode or the combined bending and twisting mode of actuation. Experimental results for actuators of different lengths were obtained for all modes of actuation and the actuator is capable of large deformations in all modes and directions of actuation. Then a simple FEA model was used to predict the range of deformation for different lengths in the different modes of actuation. This model is able to predict accurately the bending and twisting angles of the actuator for the different modes of actuation. The 120 mm actuator is capable of deformations up to approximately 160° in both the pure bending and pure twisting modes and of approximately 80° for both twisting and bending in the combined twisting and bending mode of actuation.